Inventing and naming America: Place and Place Names in Vladimir Nabokov’s Lolita - Monica Manolescu-Oancea (European Journal of American Studies)
In the afterword to Lolita, Nabokov claimed that in this book he had to invent both Lolita and America after having invented Europe in his previous fiction. This paper focuses precisely on the various ways in which Nabokov “invented” America in his best-known novel. This invention is first of all the result of the author’s evolving stance on the complexity of what he called “average ‘reality’” in his works. Through a survey of Nabokov’s statements on the choice and role of place in the forewords to his Russian works and in his critical texts, I show that Lolita is indeed considered by Nabokov to be a “recreation” of American reality, to a much greater extent than his Russian works had been recreations of a given milieu. I take the metaphor of the “crazy quilt” mentioned in Lolita to suggest complexity, chromatic exuberance, hybridity. The invention of America is also the result of a process of naming. Place names will be examined, not only those which make up Quilty’s “cryptogrammic paperchase”, but also Humbert’s choice of place names. The problem of referentiality is discussed and the way recent criticism has dealt with it. Finally, the interplay between one and many is emphasized, the way in which the diversity of the “crazy quilt” is counterbalanced by the uniqueness of the mastermind having produced it. The American motto “From many make one” could be reinterpreted as “From one make many”.